Outcome of Max Page Muscle Sliding Operation for the Treatment of Moderate Volkmann’s Ischemic Contracture of the Forearm (Journal of Pakistan Orthopaedic Association, 2020)
Background Volkmann’s ischemic contracture (VIC) is a disabling condition of the extremities and is quite common condition. When this condition sets in, the prognosis is almost always guarded, despite vigorous physical therapy and a variety of reconstructive surgeries. This study was done to assess the outcome of Max Page muscle sliding operation in VIC (moderate degree) of the forearm.Materials and methods. A single-center retrospective review of Volkmann’s ischemic contracture patients operated between 2010 and 2018 was carried out at National Orthopedic Hospital Bahawalpur. Thirty three patients were selected meeting the inclusion criteria. The functional outcome (measured as the   sensibility score and range of motion) was analyzed pre- and postoperatively. At the end of the study the results were rated as either good, fair or poor.  Outcomes.Tight external bandages secondary to radius and ulna fracture was the main cause in majority of patients. Mean time to operation was 10.81 ±2.46 months whereas mean follow up was 13.09 ±7.60 months. By applying t-test, it was found that the improvement in sensibility score and range of motion was statistically significant (P